Long-Term Functional Outcomes and Quality of Life After Microvascular Reconstruction of Ankle and Foot Defects: A Monocentric Controlled Cohort Study - Sarah Pfeifenberger; Andrzej Hecker; Nikolaus Watzinger; Maximilian Moshammer; Anna-Lisa Pignet; Alexander Draschl; Ron Martin; Charalambos Louca; Lars-Peter Kamolz; Stephan Spendel (Life)
Background: Defects of the foot and ankle area pose a significant challenge for both patients and surgeons. While the primary objective of microvascular free flap reconstructions of lower leg defects is limb preservation, there should be an effort to obtain the best functional and aesthetic results possible and to restore the patient’s quality of life. The aim of this study was to investigate the long-term post-operative functional outcome, health-related quality of life, scar quality, and aesthetic satisfaction in patients following microsurgical reconstructions of defects of the foot and ankle area. Methods: We conducted a monocentric, controlled cohort study of adult patients who underwent microsurgical reconstructions for defects of the foot and ankle area between 2006 and August 2022 at our department. As a control, we recruited healthy individuals. Patient-Reported Outcome Measures questionnaires were used to assess long-term results regarding functionality (LEFS: Lower Extremity Functional Scale), health-related quality of life (SF-36: Short-Form 36 Health Survey Questionnaire), scar quality (PSAS: Patient Scar Assessment Scale), aesthetic satisfaction (Aesthetic Likert Scale), pain at rest and activity (10-point Numeric Rating Scale) and usage of footwear. Results: Of the 55 potential patients who had received microvascular free flaps for reconstructions of ankle and foot defects and were eligible for study inclusion, 13 (23.6%) agreed to participate in this study. The study cohort consisted of 84.6% male subjects and the mean follow-up period was 8.6 years (±5.2). Significant moderate limitations were observed with regard to physical function of the lower extremity (LEFS: 42.5 ± 20.5, p = 0.002). Significant limitations were found in the SF-36 subscales of pain (55.8 ± 34.5, p = 0.019), physical functioning (55.0 ± 29.7, p = 0.013), and physical role functioning (38.5 ± 44.0, p = 0.006). The study yielded favorable outcomes with regard to aesthetic satisfaction (14.3 ± 4.4) and scar quality (23.5 ± 13.5). Out of all the patients, 61% were required to wear orthopedic shoes or insoles. Conclusions: Patients undergoing microsurgical reconstructions for ankle and foot defects experience moderate long-term physical limitations and persistent pain during activity. Furthermore, we observed a significant long-term impact on specific physical domains of health-related quality of life, whereas mental health seems less affected.